Analysis Perceived Value, Brand Packaging, Brand Trust of Purchase Intention in Shopee Marketplace, Moderated by Gender Differences - Laksmi Saraswati (Akademi Sekretari Manajemen Taruna Bakti, 2021)
Society has determined the traits that are masculine and feminine, which might affect their decision making and purchase intention. Understanding the difference between male and female regarding their purchase intention and behavior is growing. Accordingly, this paper outlines three main factors that may affect male and female purchase intention (perceived value – brand packaging – brand trust). The criteria of the population in this study are consumers of Shopee. The sampling technique used purposive sampling and the method of collecting data through online questionnaires to 100 respondents who were in accordance with the criteria of the population. Structural Equation Modeling (SEM) was used to test the hypotheses. Based on the Descriptive Analysis results, Perceived value is in “good” category with percentage value 79%, brand packaging is in “good” category with percentage value 76%, and brand trust is in “good” category with percentage value 76%. All the main factors (perceived value – brand packaging- brand trust) are have a significant effect to purchase intention, meanwhile the differences of gender (male and female) doesn’t show a moderating effect to purchase intention. So there are a same perception of purchase intention between male and female customer.